Process control performance evaluation in the case of variable set‐point with experimental applications. (1st August 2017) - Bacci di Capaci, Riccardo; Scali, Claudio
Abstract: The purpose of this paper is to contribute with some refinements to recent methods of analysis of control loop performance, based on the well‐established principle of Internal Model Control (IMC). Lower limits for the absolute value of the integral of control error (IAE) and the total variation of control action (TV) are assumed as reference values for a control considered good or at least acceptable. The overall performance index assumes as a benchmark a controller tuned according to rules of S(implified)IMC technique and is appropriately defined with respect to the lower limits of the two metrics IAE and TV. This allows the assessment of control loop performance, that is, the validity of tuning for PID‐type controllers in response to different types of reference change. In fact, one can assess performance in the case of set‐point changes as steps, ramps, or generic varying trends over time. In order to demonstrate the validity of the refined technique, several examples of simulation, case studies on a pilot plant, and real industrial data are presented.